Penerapan Pengolahan Ikan Patin dan Daun Kelor Menjadi Mi Instan di Desa Mekar Sari Kecamatan Maro Sebo Ulu - Hardiani; Junaidi; Hastuti, Dwi; Umiyati, Etik; Parok, Al (WIDA Publishing, 2023)
The high consumption of noodles has made noodles popular as instant or fast food. Its high demand has led to the production of various noodle variants, including low-carb and high-vitamin noodles.One of innovations is catfish-based and moringa leaves-based noodle which has been successfully carried out through the Pro Ide scheme by Diploma IV Keuangan Daerah students in the Faculty of Economics and Business, Universitas Jambi (FEB UNJA). This innovation has gained Intellectual Property Rights (HKI). FEB UNJA lecturers and students are involved in community service in Mekar Sari Village, Maro Sebo Ulu District, Batang Hari Regency, Jambi Province. The team developed the potential of the Batang Hari river and ponds, especially catfish and carp farming. This opens up opportunities for product diversification and downstreaming of fish into noodles. The development of a business model has great potential through innovations that enable knowledge and technology transfer. In addition, this business model focuses on capacity building, technology transfer, market access, and empowerment of Village-Owned Enterprises (BUMDes), one of which is by making noodles with catfish and moringa leaves as the main ingredients.